Seeding Chiral Ensembles of Prolinated Porphyrin Derivatives on Glass Surface: Simple and Rapid Access to Chiral Porphyrin Films - Magna, Gabriele; Traini, Tanja; Naitana, Mario Luigi; Bussetti, Gianlorenzo; Domenici, Fabio; Paradossi, Gaio; Venanzi, Mariano; Di Natale, Corrado; Paolesse, Roberto; Monti, Donato; Stefanelli, Manuela (Frontiers in Chemistry, 2022)
An easy and fast method to achieve chiral porphyrin films on glass is herein reported. The on-surface formation of organized supramolecular architectures with distinctive and remarkable chiroptical features strictly depends on the macrocycles used, the solvent chosen for the casting deposition and most importantly, on the roughness of the glass slide. Dynamic Light Scattering (DLS) studies performed on 10-4-10-6 M porphyrin solutions revealed the presence of small porphyrin aggregates, whose size and number increase depending on the initial concentration. Once transferred on surface, these protoaggregates act as nucleation seeds for the following self-assembling into larger structures upon solvent evaporation, with a process driven by a fine balance between intermolecular and molecule-substrate interactions. The described method represents a straightforward way to fabricate porphyrin-based chiral surfaces onto a transparent and economic substrate in few minutes. The results obtained can be particularly promising for the development of sensors based on stereoselective optical active films, targeting the detection of chiral analytes of practical relevance, such as the so-called emerging pollutants released in the environment from agrochemical, food, and pharmaceutical manufacturing.